Lentivirus‐Mediated α‐Melanocyte‐Stimulating Hormone Overexpression in the Hypothalamus Decreases Diet Induced Obesity in Mice. (25th November 2013) - Eerola, K.; Nordlund, W.; Virtanen, S.; Dickens, A. M.; Mattila, M.; Ruohonen, S. T.; Chua, S. C.; Wardlaw, S. L.; Savontaus, M.; Savontaus, E.
Abstract : Melanocyte stimulating hormone (MSH) derived from the pro‐hormone pro‐opiomelanocortin (POMC) has potent effects on metabolism and feeding that lead to reduced body weight in the long‐term. To determine the individual roles of POMC derived peptides and their sites of action, we created a method for the delivery of single MSH peptides using lentiviral vectors and studied the long‐term anti‐obesity effects of hypothalamic α‐MSH overexpression in mice. An α‐MSH lentivirus (LVi‐α‐MSH‐EGFP) vector carrying the N'‐terminal part of POMC and the α‐MSH sequence was generated and shown to produce bioactive peptide in an in vitro melanin synthesis assay. Stereotaxis was used to deliver the LVi‐α‐MSH‐EGFP or control LVi‐EGFP vector to the arcuate nucleus (ARC) of the hypothalamus of male C57Bl/6N mice fed on a high‐fat diet. The effects of 6‐week‐treatment on body weight, food intake, glucose tolerance and organ weights were determined. Additionally, a 14‐day pairfeeding study was conducted to assess whether the weight decreasing effect of the LVi‐α‐MSH‐EGFP treatment is dependent on decreased food intake. The 6‐week LVi‐α‐MSH‐EGFP treatment reduced weight gain (8.4 ± 0.4 g versus 12.3 ± 0.6 g; P < 0.05), which was statistically significant starting from 1 week after the injections. The weight of mesenteric fat was decreased and glucose tolerance was improved compared to LVi‐EGFP treated mice. Food intake was decreased during the first week in the LVi‐α‐MSH‐EGFP treated mice but subsequently increased to the level of LVi‐EGFP treated mice. The LVi‐EGFP injected control mice gained more weight even when pairfed to the level of food intake by LVi‐α‐MSH‐EGFP treated mice. We demonstrate that gene transfer of α‐MSH, a single peptide product of POMC, into the ARC of the hypothalamus, reduces obesity and improves glucose tolerance, and that factors other than decreased food intake also influence the weight decreasing effects of α‐MSH overexpression in the ARC. Furthermore, viral MSH vectors delivered stereotaxically provide a novel tool for further exploration of chronic site‐specific effects of POMC peptides.